1984
DOI: 10.1080/02571862.1984.10634108
|View full text |Cite
|
Sign up to set email alerts
|

A complex dormancy mechanism in seeds of the weedRubus cuneifolius

Abstract: A complex dormancy mechanism in seeds of the weed Rubus cunei/o/ius J. van StadenDepartment of Botany, University of Natal Peta L. Campbell Plant Protection Research Institute, PietermaritzburgBoth the endocarp and embryo contribute to the dormancy of Rubus cuneifolius seed. Whereas scarification was found to break the dormancy imposed by the endocarp, embryo dormancy could only be overcome by a combination of treatments. These treatments consisted of a one·month stratification period followed by incubation at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Second, cutting the endocarp was found to promote germination, consistent with van Staden and Campbell (1984) who found that germination in R. cuneifolius could be achieved as long as the endocarp was scarified through cutting, or acid treatment. In contrast, acid treatment of the endocarp did not improve germination in R. anglocandicans, which was consistent with previous studies in a number of blackberry species (Wada and Reed 2011b;Choi et al 2016).…”
Section: Initial Factors Influencing Germinationsupporting
confidence: 76%
See 3 more Smart Citations
“…Second, cutting the endocarp was found to promote germination, consistent with van Staden and Campbell (1984) who found that germination in R. cuneifolius could be achieved as long as the endocarp was scarified through cutting, or acid treatment. In contrast, acid treatment of the endocarp did not improve germination in R. anglocandicans, which was consistent with previous studies in a number of blackberry species (Wada and Reed 2011b;Choi et al 2016).…”
Section: Initial Factors Influencing Germinationsupporting
confidence: 76%
“…Choi et al (2016) found that for R. parvifolius, R. phoenicolasius, and R. takesimensis scarification (with sulphuric acid) needed to be combined with cold stratification (8 weeks at 4°C) to improve germination, owing to physiological dormancy reported in these species (Bewley et al 2013), whereas other species such as R. buergeri and R. corchorifolius did not respond to any imposed treatments. In contrast, van Staden and Campbell (1984) found that the most effective treatment of R. cuneifolius was immersion in concentrated sulfuric acid for 1.5 h. In R. anglocandicans, the physical suppression of germination still held despite acid treatments and germination occurred only once the endocarp was removed or damaged. Such variability in germination requirements reinforces the findings of previous studies that there are few generalisations to make for germination requirements among Rubus species.…”
Section: Initial Factors Influencing Germinationmentioning
confidence: 93%
See 2 more Smart Citations